The intellectual relationship of cash flows, financial solvency, profitability and liquidity ratio to the auditor’s assessment of the company’s ability to continue: A field study on public joint-stock companies in Jordan - Dr. Hani Ali Al-Rawashdeh*; Dr. Alaa Muhammad Ahmed Rabie; Prof. Dr. Muhammad Fawzi Abu Al-Hayjaa; أ.د.أسامة عبدالمنعم علي; Dr. Ibrahim Youssef Al-Abadi (مجلة الدراسات الاقتصادية والادارية)
This study aims to analyze the financial characteristics that affect the ability of Jordanian public shareholding companies to maintain their continuity. To achieve this, the researchers adopted a correlational approach, which allows for examining the relationships between two or more variables. The study population consisted of 221 public shareholding companies, from which a representative sample of all sectors with available required data was selected, totaling 158 companies. The study’s hypotheses were subjected to multiple tests, including the use of statistical means and standard deviations, as well as regression analysis to test the hypotheses. Among the main findings of the study, it was revealed that both company liquidity and financial solvency significantly impact the decisions of auditors of Jordanian public shareholding companies when issuing audit reports indicating a lack of continuity. The study also provided a set of recommendations, the most important of which is that auditors should consider financial indicators, such as solvency and liquidity ratios, as key factors in assessing a company's ability to continue operating. Additionally, further research should be conducted on non-financial factors and indicators that influence auditors when issuing their reports on a company's continuity.